Intentional rounding: a realist evaluation using case studies in acute and care of older people hospital wards - Mary Leamy; Sarah Sims; Ros Levenson; Nigel Davies; Sally Brearley; Stephen Gourlay; Giampiero Favato; Fiona Ross; Ruth Harris (BMC, 2023)
Abstract Background In response to concerns about high hospital mortality rates, patient and carer complaints, a Mid Staffordshire NHS Foundation Trust public inquiry was conducted at the request of the UK government. This inquiry found serious failures in the quality of basic care provided and as a consequence, recommended that patients should have more regular visits, organised at predictable times from nursing staff. Intentional rounding, also known as nursing ward rounds, was widely adopted to meet this need. Objective To test, refine or refute eight programme theories to understand what works, for whom, and in what circumstances. Setting Six wards (older people and acute wards) in three NHS trusts in England. Participants Board level and senior nursing managers (N = 17), nursing ward staff (N = 33), allied health and medical professionals (N = 26), patients (N = 34) and relatives (N = 28) participated in an individual, in-depth interview using the realist method. In addition, ward-based nurses (N = 39) were shadowed whilst they conduced intentional rounds (240 rounds in total) and the direct care of patients (188 h of patient care in total) was observed. Methods The mixed methods design included: Phase (1) Theory development - A realist synthesis was undertaken to identify any programme theories which were tested, refined and/or refuted, using data from phases 2 and 3; Phase (2) A survey of all English NHS acute Trusts; Phase (3) Six case studies of wards involving realist interviews, shadowing and non-participant observations, analysis of ward outcome and cost data; and Phase (4) Synthesis of findings from phases 1, 2 and 3. Results The realist synthesis identified eight programme theories of intentional rounding: 'Consistency and comprehensiveness', 'Accountability', 'Visibility of nurses', 'Anticipation', 'Allocated time to care', 'Nurse-patient relationships', 'Multi-disciplinary teamwork and communication' and 'Patient empowerment'. Key findings showed that of the original eight programme theories of intentional rounding, only two partially explained how the intervention worked ('Consistency and comprehensiveness' and 'Accountability'). Of the remaining six programme theories, the evidence for two was inconclusive ('Visibility of nurses' and 'Anticipation') and there was no evidence for four ('Allocated time to care'; 'Nurse-patient relationships'; 'Multi-disciplinary teamwork and communication'; and 'Patient empowerment'). Conclusions This first theory-informed evaluation of intentional rounding, demonstrates that the effectiveness of intentional rounding in the English healthcare context is very weak. Furthermore, the evidence collected in this study has challenged and refuted some of the underlying assumptions about how intentional rounding works. This study has demonstrated the crucial role context plays in determining the effectiveness of an intervention and how caution is needed when implementing interventions developed for the health system of one country into another.